THE EFFECT OF EXPLAINER VIDEO LEARNING MEDIA ON STUDENTS’ LEARNING OUTCOMES IN AQIDAH AKHLAK SUBJECT - Afifah, Rina Noer; Rochmat, Cecep Sobar (Jurnal Ilmiah Pendidikan Citra Bakti, 2026)
The Aqidah Akhlak subject plays an important role in shaping students’ character through strengthening faith and fostering the habituation of noble morals in daily life. However, many students experience difficulties in understanding Aqidah concepts and applying moral values, resulting in learning outcomes that have not yet met the Minimum Mastery Criteria (MMC). This condition is influenced by instructional practices that tend to be theoretical and are not sufficiently supported by engaging and interactive learning media. Therefore, this study aims to examine the effect of using Explainer video as an interactive learning medium on students’ learning outcomes in the Aqidah Akhlak subject for eighth-grade students at MTs Negeri 4 Madiun, East Java, in the 2025–2026 academic year. This study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The population consisted of all eighth-grade students, with a sample of 50 students selected through purposive sampling. Data were collected through learning outcome tests supported by interviews and documentation. Data analysis included tests of validity, reliability, normality, and homogeneity, as well as hypothesis testing using an independent samples t-test with the assistance of SPSS version 25. The results showed a significant difference between the experimental and control classes, with a Sig. (2-tailed) value of 0.000 (< 0.05). The mean post-test score of the experimental class was 96.08 ± 2.857, while that of the control class was 81.12 ± 3.206. The improvement in the experimental class was also evident from the increase in the mean score from 58.56 in the pre-test to 91.24 in the post-test, while the control class improved from 65.24 to 81.12. These findings indicate that the use of Explainer video as a learning medium has a positive and significant effect on students’ learning outcomes in the Aqidah Akhlak subject.